Customs compliance and the power of imagination - Kai A. Konrad; Tim Lohse; Salmai Qari (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper studies the role of beliefs about own performance or appearance for compliance at the customs. In an experiment in which underreporting has a higher expected payoff than truthful reporting we find: a large share, about 15-20 percent of the subjects, is more compliant if they have reason to imagine that their performance influences their subjective audit probability. In contrast, we do not find evidence for individuals who believe that by their personal performance they can reduce the subjective probability for an audit. Our results suggest that the power of imagination, i.e. the role of second-order beliefs in the process of customs declarations is important and may potentially be used to improve customs and tax compliance.
Keywords: H26; H31; C91; 330; customs; tax compliance; audit probability; second-order beliefs; Zoll; Steuermoral; Steuerfahndung; Wahrnehmung; Test; Deutschland